Kepadatan Makrozoobentos di Perairan Sungai Desa Toaya Kecamatan Sindue Kabupaten Donggala - Nurhaliza, Siti; Bustamin, Bustamin; Rauf, Abd.; Nurdin, Musdalifah; Sabran, Moh.; Agni, Raya (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study aims to determine the density of macrozoobenthos in Toaya Village River Waters. This study uses a Quantitative Descriptive method with purposive sampling location determination consisting of 3 observation stations and sampling using the line Transect technique with a surber net sampling tool. Data analysis is done by calculating the density of samples that have been obtained in the field using the density formula. The results showed that (1) 5 types of macrozoobenthos were identified in the waters of Toaya Village River with the highest density at Station I (9.17 ind/mÂ²) and the lowest at Station III (6.25 ind/mÂ²). (2) These density differences reflect variations in environmental conditions, such as bottom substrate, water currents, pollution levels, and availability of organic matter. (3) Environmental conditions at station 1 are relatively more favorable for benthic organisms, while stations II and III reflect environmental pressures such as pollution or changes in habitat quality. Thus, macrozoobenthos acts as an effective bioindicator to assess water quality, so these results reflect the health level of the river ecosystem.